2007
DOI: 10.1136/ard.2006.054742
|View full text |Cite
|
Sign up to set email alerts
|

Do rheumatoid arthritis patients in clinical practice benefit from switching from infliximab to a second tumor necrosis factor alpha inhibitor?

Abstract: LOE switchers had a better clinical response to the second treatment. AE switchers responded equally well to both treatments, with a low risk of discontinuing the second drug as a result of AE. Drug survival of the switchers' second biological therapy was higher than of the first, but lower than that of non-switchers. No difference between various sequences of drugs were found. Danish post-marketing data thus support that RA patients may benefit from switching biological therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
1
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(64 citation statements)
references
References 15 publications
5
54
1
4
Order By: Relevance
“…There was little information about baseline characteristics; however, it seems that there may be some, if small, differences between studies. The main results of included studies are summarised in 110 Duftner et al 111 and Karlsson et al 112 patients switched TNF inhibitorsowing to lack of efficacy or AEs or for other reasons. The reason for changing from one TNF inhibitor to another was unclear in Solau-Gervais et al 109 Hyrich et al [121][122][123] used data from the BSRBR.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There was little information about baseline characteristics; however, it seems that there may be some, if small, differences between studies. The main results of included studies are summarised in 110 Duftner et al 111 and Karlsson et al 112 patients switched TNF inhibitorsowing to lack of efficacy or AEs or for other reasons. The reason for changing from one TNF inhibitor to another was unclear in Solau-Gervais et al 109 Hyrich et al [121][122][123] used data from the BSRBR.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies reported median drug survival. 110,111 Hjardem et al 110 and Duftner et al 111 reported that the median drug survival was 37 weeks and 8.0 months (range 0-43.7 months), respectively.…”
Section: Withdrawalsmentioning
confidence: 99%
See 2 more Smart Citations
“…[84][85][86] An analysis of the Danish Database for Biological Therapies in Rheumatology (DANBIO) showed that patients with RA benefit from the switching of anti-TNF drugs. [87] Active RA patients refractory to DMARD or TNF blockers were included in a rituximab meta-analysis, and ACR 20, 50, and 70 responses were evaluated. Rituximab and MTX combination treatment was found to be effective and associated with low adverse effect incidence in refractory cases.…”
Section: Depending On the Clinical Characteristics In Dmard-naive Patmentioning
confidence: 99%